2018
DOI: 10.1002/aocs.12042
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Flaxseed Protein Hydrolysates: Influence of Hydrolytic Enzyme Concentration and Peptide Size

Abstract: Flaxseed is an emerging source of protein raw materials for bioactive protein hydrolysate production; however, there is insufficient information on the structural properties of its antioxidative peptides. The aim of this work was to determine the peptide composition and relationships to antioxidant properties of flaxseed protein hydrolysates (FPH) obtained using two protease (thermoase) concentrations (2.5 and 3.0%). The FPH were passed through ultrafiltration membranes to yield fractions with <1, 1-3, 3-5, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
4
24
1
Order By: Relevance
“…Comparatively, the findings from the present study is similar to the observation of other researchers, which suggest stronger DRSA for LMW peptide fractions than HMW peptides and crude hydrolysate (Arise et al, 2016;Jha, Mandal, Bhattacharyya, & Ghosh, 2014;Sonklin, Laohakunjit, & Kerdchoechuen, 2018). Nwachukwu and Aluko (2018) been identified as important assays to predict antioxidant activities (Islam et al, 2013). Therefore, the strong ability of PPHT and peptide fractions to scavenge these radicals is a pointer to their potential relevance as sources of natural antioxidant and functional ingredients.…”
Section: Antioxidant Activity Of Protein Hydrolysate and Membrane Fsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparatively, the findings from the present study is similar to the observation of other researchers, which suggest stronger DRSA for LMW peptide fractions than HMW peptides and crude hydrolysate (Arise et al, 2016;Jha, Mandal, Bhattacharyya, & Ghosh, 2014;Sonklin, Laohakunjit, & Kerdchoechuen, 2018). Nwachukwu and Aluko (2018) been identified as important assays to predict antioxidant activities (Islam et al, 2013). Therefore, the strong ability of PPHT and peptide fractions to scavenge these radicals is a pointer to their potential relevance as sources of natural antioxidant and functional ingredients.…”
Section: Antioxidant Activity Of Protein Hydrolysate and Membrane Fsupporting
confidence: 91%
“…Comparatively, the findings from the present study is similar to the observation of other researchers, which suggest stronger DRSA for LMW peptide fractions than HMW peptides and crude hydrolysate (Arise et al., 2016; Jha, Mandal, Bhattacharyya, & Ghosh, 2014; Sonklin, Laohakunjit, & Kerdchoechuen, 2018). Nwachukwu and Aluko (2018) reported that membrane ultrafiltration improved DRSA of thermoase hydrolysate of flaxseed protein, although, there was no significant difference ( p > .05) in the activity of the different peptide sizes. Similarly, Rong, Girgih, Malomo, Ju, and Aluko (2013) earlier reported that membrane ultrafiltration promoted antioxidant activities of rapeseed peptides.…”
Section: Resultsmentioning
confidence: 98%
“…The FRAP assay is routinely used to determine ability of antioxidative food protein‐derived hydrolyzates and peptides to serve as reductants by donating their excess electrons to the Fe 3+ ‐2,4,6‐tripyridyl‐S‐triazine complex, and reducing it to the more stable divalent ferrous ion, Fe 2+ (He et al, ; Nwachukwu & Aluko, ; Torres‐Fuentes et al, ). In a study of protein hydrolyzates and peptides from Corolase PP‐hydrolyzed sea lettuce flakes ( P. palmata ), the high reducing power of the decapeptide, SDITRPGGNM was linked to the terminal Met residue (Harnedy et al, ) because sulfur‐containing amino acids, such as Cys and Met are known to be highly effective in reducing the Fe 3+ ‐ferricyanide complex (Udenigwe & Aluko, ).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…In addition, antioxidant peptides could also serve as additives in foods in order to curb the oxidation of food products (Qiu, Chen, & Dong, ). This is especially useful to prevent oxidative rancidity of foods containing oils where the formation of ketones and aldehydes could impair the food's organoleptic properties, shorten its shelf life and result in considerable economic losses (He et al, ; Nwachukwu & Aluko, ; Qiu et al, ). The ability of such protein‐derived antioxidative agents to play a role in the prevention and/or amelioration of ROS‐induced oxidative damage has been increasingly linked to their structural properties (Aluko, ; Samaranayaka & Li‐Chan, ; Zou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of membrane fractionation technologies include nanofiltration and ultrafiltration, the latter being the most utilized to date for peptide fractionation. A plethora of studies have demonstrated the significance of ultrafiltration for fractionating peptides from several food protein hydrolyzates such as pea protein hydrolyzates (Li et al, ), egg ovomucin hydrolyzates (Sun, Chakrabarti, Fang, Yin, & Wu, ), flaxseed protein hydrolyzates (Nwachukwu & Aluko, ), and chicken feather keratin hydrolyzates (Yeo et al, ).…”
Section: Structure‐informed Separation Processesmentioning
confidence: 99%